Strengthening Hospital Competitiveness to Improve Patient Satisfaction and Better Health Outcomes 2019
DOI: 10.26911/the6thicph.02.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nurse Therapeutic Communication on Satisfaction among The Families Of Schizophrenic Patients At Prof Muhammad Ildrem Mental Hospital, Medan, North Sumatra

Abstract: Background: Therapeutic communication is the primary component of all health care interaction that facilitates the development of positive clinician-patient experiences. Nurses with the skills to communicate not only will be easily establish a trusting relationship with the patients but also patients' families. Therapeutic communication is known to be necessary for quality healthcare and increase patient satisfaction. This study aimed to examine the effect of nurse therapeutic communication on satisfaction amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The research done by Pasaribu (2004) in Suka Village, TigaPanah district, Karo Regency, North Sumatra, Indonesia, showed that the prevalence of helminthiasis in schoolchildren was 91.3% [5]. The performance accountability report of North Sumatra government health agency (2012) stated that the prevalence of STH infections in primary schoolchildren was 32.3%, with the distribution of A. lumbricoides and T. trichiura and hookworms species at 21%, 11%, and 0%, respectively [6]. Another study done by Jiero et al (2015) in Medan, Belawan, North Sumatra in two primary schools showed 65.4% prevalence of STH infections [7].…”
Section: Introductionmentioning
confidence: 99%
“…The research done by Pasaribu (2004) in Suka Village, TigaPanah district, Karo Regency, North Sumatra, Indonesia, showed that the prevalence of helminthiasis in schoolchildren was 91.3% [5]. The performance accountability report of North Sumatra government health agency (2012) stated that the prevalence of STH infections in primary schoolchildren was 32.3%, with the distribution of A. lumbricoides and T. trichiura and hookworms species at 21%, 11%, and 0%, respectively [6]. Another study done by Jiero et al (2015) in Medan, Belawan, North Sumatra in two primary schools showed 65.4% prevalence of STH infections [7].…”
Section: Introductionmentioning
confidence: 99%